EFFECTIVE METHODS OF CARE FOR SUNFLOWER CROPS - Nasiyev B.N, (Academic Journal of Physical and Chemical Sciences, 2021)
Sunflower cultivation is relevant in the climatic conditions of Western Kazakhstan, characterized by high heat supply and a long growing season. In order to obtain a high yield of sunflower in the system of adaptive technologies, proper pre-sowing preparation of the soil and optimal sowing times are important. Weeds cause great damage to the sunflower crop. Having a powerful underground and aboveground mass, sunflower competes with weeds better than many other field crops. As the accounting data showed, in our studies of 2018-2020, the greatest contamination of sunflower crops was in the variants without the use of herbicides. So, on average for 3 years in the phase 2 of real leaves, when using the harrowing + pre-sowing cultivation (control) technology, there were 10.67 weeds per 1 m2 with a raw mass of 31.22 g/m2 . According to research data, on average for 2018-2020, the highest oil harvest is set for the harrowing + pre-sowing cultivation option with roundup (2 l/ha) – 9.57 с/ha. When using 1 and 2 inter-row treatments combined with harrowing and pre-sowing cultivation, the oil harvest increased to 7.16-7.95 с/ha, which is more than the control by 0.92-1.71 с/ha.